Insight into Physiological and Biochemical Determinants of Salt Stress Tolerance in Tetraploid Citrus - Marie Bonnin; Bénédicte Favreau; Alexandre Soriano; Nathalie Leonhardt; Julie Oustric; Radia Lourkisti; Patrick Ollitrault; Raphaël Morillon; Liliane Berti; Jérémie Santini (MDPI AG, 2023)
Citrus are classified as salt-sensitive crops. However, a large diversity has been observed regarding the trends of tolerance among citrus. In the present article, physiological and biochemical studies of salt stress tolerance were carried out according to the level of polyploidy of different citrus genotypes. We particularly investigated the impact of tetraploidy in trifoliate orange (Poncirus trifoliata (L.) Raf.) (PO4x) and Cleopatra mandarin (Citrus reshni Hort. Ex Tan.) (CL4x) on the tolerance to salt stress compared to their respective diploids (PO2x and CL2x). Physiological parameters such as gas exchange, ions contents in leaves and roots were analyzed. Roots and leaves samples were collected to measure polyphenol, malondialdehyde (MDA), ascorbate and H2O2 contents but also to measure the activities of enzymes involved in the detoxification of active oxygen species (ROS). Under control conditions, the interaction between genotype and ploidy allowed to discriminate different behavior in terms of photosynthetic and antioxidant capacities. These results were significantly altered when salt stress was applied when salt stress was applied. Contrary to the most sensitive genotype, that is to say the diploid trifoliate orange PO2x, PO4x was able to maintain photosynthetic activity under salt stress and had better antioxidant capacities. The same observation was made regarding the CL4x genotype known to be more tolerant to salt stress. Our results showed that tetraploidy may be a factor that could enhance salt stress tolerance in citrus.